Enzyme‐Driven Hasselback‐Like DNA‐Based Inorganic Superstructures. (24th October 2017) - Lee, Jae Sung; Kim, Hyejin; Jo, Changshin; Jeong, Jaepil; Ko, Jeonghyun; Han, Sangwoo; Lee, Min Sun; Lee, Ho‐Young; Han, Jeong Woo; Lee, Jinwoo; Lee, Jong Bum
Abstract: DNA structures have gained much attention due to its ease of self‐assembly and precise controllability. Although DNA technology has been successfully applied to generate a variety of DNA structures, there are only few attempts to apply DNA technology to generate inorganic materials due to lack of controllability of interactions between DNA and inorganic materials. In addition, the synthesis of a predictable structure of hybrid materials still remains a significant challenge. To address the challenge, here a novel strategy for the synthesis of DNA‐based inorganic superstructures using DNA polymerase is reported. In particular, strategic feeding of metal ions for generating DNA‐inorganic hybrid superstructures during DNA polymerization is established. This approach can produce a variety of structures with varying metal ions and can easily add functionality to the product. The structural features are also easily studied by first‐principles calculations. With these advantages, DNA‐Mn particles show the potential as a cell tracking agent, a contrast agent for MRI, and an electrode material for supercapacitors. The enzyme‐driven synthesis in this study will provide a novel route for the generation of a range of organic–inorganic hybrid superstructures for biomedical and energy applications. Abstract : A novel strategy for enzymatic synthesis of DNA‐based inorganic micro/nanostructures is developed with a highly precise control of morphologies, components, and functionalities by employing the continuous pyrophosphate feeding system via DNA polymerase.